2008
DOI: 10.1176/appi.ajp.2008.07101574
|View full text |Cite
|
Sign up to set email alerts
|

Brain and Plasma Pharmacokinetics of Aripiprazole in Patients With Schizophrenia: An [ 18 F]Fallypride PET Study

Abstract: Because of its high affinity for D(2)/D(3) receptors and its long elimination half-life, aripiprazole at clinical doses occupies a high fraction of its target receptor everywhere in the brain. Its dissociation from those receptors is very slow, such that the authors calculate from the results that in patients with serum aripiprazole concentrations in the range typical for clinical practice, D(2)/D(3) receptors must remain nearly saturated for as long as 1 week after the last dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 37 publications
8
88
0
1
Order By: Relevance
“…The relatively low occupancy required for the partial agonist ABT-089 in animal models contrasts with the much higher level of occupancy required for the D 2 -partial agonist aripiprazole. Aripiprazole has been recently approved for treating psychiatric disorders and requires 90% receptor occupancy to achieve efficacy in preclinical animal models (Natesan et al, 2006) as well as in patients with schizophrenia (Grü nder et al, 2008). Unlike other D 2 -partial agonists that failed in clinical development, aripiprazole has high affinity for D 2 /D 3 receptors and a long plasma half-life, which leads to high-receptor occupancy over a long period time (Grü nder et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively low occupancy required for the partial agonist ABT-089 in animal models contrasts with the much higher level of occupancy required for the D 2 -partial agonist aripiprazole. Aripiprazole has been recently approved for treating psychiatric disorders and requires 90% receptor occupancy to achieve efficacy in preclinical animal models (Natesan et al, 2006) as well as in patients with schizophrenia (Grü nder et al, 2008). Unlike other D 2 -partial agonists that failed in clinical development, aripiprazole has high affinity for D 2 /D 3 receptors and a long plasma half-life, which leads to high-receptor occupancy over a long period time (Grü nder et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Aripiprazole has been recently approved for treating psychiatric disorders and requires 90% receptor occupancy to achieve efficacy in preclinical animal models (Natesan et al, 2006) as well as in patients with schizophrenia (Grü nder et al, 2008). Unlike other D 2 -partial agonists that failed in clinical development, aripiprazole has high affinity for D 2 /D 3 receptors and a long plasma half-life, which leads to high-receptor occupancy over a long period time (Grü nder et al, 2008). The difference in receptor occupancy required for these two partial agonists is probably related to differences in the role of dopaminergic transmission in psychosis and nicotinic cholinergic transmission in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…Haloperidol's plasma half-life is 14.5-36.7 hours in humans (de Leon et al, 2004), but 1.5 hours in rats (Cheng and Paalzow, 1992). Aripiprazole has a long plasma elimination half-life (60-70 hours) in humans (Grunder et al, 2008), while in rats aripiprazole reached the maximal plasma concentration (C max ) 2 hours after oral administration (10mg/kg) with an elimination half-life of 2.2 hours (Shimokawa et al, 2005). Therefore, all rats were treated three times per day, at 06:00, 14:00, and 22:00 h, orally by administering specially prepared sweet cookie dough pellets (0.3g) to ensure a consistently high concentration to better mirror the human scenario of oral administration once per day (Deng et al, 2012;Han et al, 2008;Weston-Green et al, 2011).…”
Section: Animals and Drug Treatmentmentioning
confidence: 99%
“…22,34,35 Aripiprazole, with its partial agonist properties, also produces values that are difficult to reconcile with what is observed clinically (i.e., lower EPS profile despite high D 2 occupancy). 36 Notwithstanding such exceptions, it has been suggested that D 2 occupancy levels may represent the most empiric means of establishing dose equivalents, at least in terms of antipsychotic activity given the central role D 2 blockade appears to play in this symptom domain. 37 Establishing dosing based on D 2 occupancy has, in fact, been widely embraced in the literature, including preclinical studies 38 and drug development studies.…”
Section: Translating D 2 Occupancy To Antipsychotic Dosingmentioning
confidence: 99%